Characterization of Acid Soluble Collagen from Redbelly Yellowtail Fusilier Fish Skin (Caesio cuning) - Ika Astiana; Nurjanah Nurjanah; Tati Nurhayati (Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
Fish skin can be used as raw material for producing collagen. The collagen can be extracted by chemicalor combination of chemical and enzymatic processes. Extraction of collagen chemically can do with theacid process that produces acid soluble collagen (ASC). This study aimed to determine the optimumconcentration and time of pretreatment and extraction, also to determine the characteristics of the acidsoluble collagen from the skin of yellow tail fish. Extraction of collagen done by pretreatment using NaOH atthe concentration of 0.05; 0.1; and 0.15 M and extraction using acetic acid at the concentration of 0.3; 0.5; and0.7 M. Pretreatment NaOH with concentration 0.05 M and soaking time of 8 hours is the best combinationfor eliminating non collagen protein. Combination treatment of acetic acid at the concentration of 0.3 Mfor 3 days obtained the best solubility. The yield of collagen ASC was 18.4±1.49% (db) and 5.79±0.47%(wb). Amino acid composition that is dominant in the ASC collagen was glycine (25.09±0.003%), alanine(13.71±0.075%), and proline (12.15±0.132%). Collagen from yellow tail fish skin has α1, α2, β and γprotein structure with the molecular weight of 125, 113, 170-181, and 208 KDa. The transition and meltingtemperatures of collagen were 67.69oC and 144.4oC. The surface structure of collagen by analysis of SEM hasfibers on the surface.Keywords: cholesterol, fatty acids, meat tissue, proximate, red snapper (L. argentimaculatus)